Boundedness and Compactness of Specific Weighted Composition Operators on the Zygmund-Orlicz Space - Hang Zhou (Journal of Function Spaces)
We say φ∈U if a constant Cφ>1 could be found, such that φst≤Cφsφt,s>1,t>0. Under the assumption φ∈U, boundedness and compactness of weighted composition operators on the Zygmund-Orlicz space Zφ are investigated in this paper.